2015
DOI: 10.1038/hdy.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and recombination analysis of two moth colour mutations, Black moth and Wild wing spot, in the silkworm Bombyx mori

Abstract: Many lepidopteran insects exhibit body colour variations, where the high phenotypic diversity observed in the wings and bodies of adults provides opportunities for studying adaptive morphological evolution. In the silkworm Bombyx mori, two genes responsible for moth colour mutation, Bm and Ws, have been mapped to 0.0 and 14.7 cM of the B. mori genetic linkage group 17; however, these genes have not been identified at the molecular level. We performed positional cloning of both genes to elucidate the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Expression of alternative candidate genes. Two B. mori adult melanism/patterning mutations, Black moth (Bm) and Wild wing spot (Ws), were recently mapped to a region partially orthologous to the carbonaria interval 21 . In this study, end-point PCR showed complete absence of cortex expression in pupal stages and adults but potentially important prepupal stages were not examined.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of alternative candidate genes. Two B. mori adult melanism/patterning mutations, Black moth (Bm) and Wild wing spot (Ws), were recently mapped to a region partially orthologous to the carbonaria interval 21 . In this study, end-point PCR showed complete absence of cortex expression in pupal stages and adults but potentially important prepupal stages were not examined.…”
Section: Methodsmentioning
confidence: 99%
“…Functional defects or abnormal expression of some key genes in the melanin metabolism pathway can also lead to melanism [ 6 , 9 , 10 ]. In contrast, some studies found that some melanic morphs had no variations in the classic melanin metabolism pathway genes indicating the mechanistic diversity of melanism [ 7 , 11 , 12 ]. An example for this mechanism is the industrial melanism in the peppered moth ( Biston betularia ) [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The silkworm, Bombyx mori , is the most advanced lepidopteran model with over 100 body color mutants described thus far [ 19 , 20 ]. Studies of body color mutants has enhanced our fundamental understanding of the silkworm pigmentation processes and the genetic mechanisms underlying insect melanism [ 6 , 10 , 12 , 21 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Heliconius, the locus acts across both wing surfaces and underlies variation in white, yellow, orange, and black pattern elements (Joron et al, 2006). Cortex has also been implicated in pattern variation in other butterflies (VanKuren et al, 2019), the peppered moth Biston betularia and other geometrids (van't Hof et al, 2016(van't Hof et al, , 2019, as well as the silkmoth Bombyx mori (Ito et al, 2016). Secondly, nearly all the patterning genes thus far identified are highly conserved at the amino acid level and are used extensively throughout embryonic and larval development, and later simply redeployed on a developing wing to affect pattern variation.…”
Section: Background and Overviewmentioning
confidence: 99%